2012
DOI: 10.1007/s10875-012-9699-7
|View full text |Cite
|
Sign up to set email alerts
|

CD4+LAP+ and CD4+CD25+Foxp3+ Regulatory T Cells Induced by Nasal Oxidized Low-Density Lipoprotein Suppress Effector T Cells Response and Attenuate Atherosclerosis in ApoE−/− Mice

Abstract: Increasing studies have demonstrated that atherosclerosis is a chronic immunoinflammatory disease, and that oxidized low-density lipoprotein (oxLDL)-specific T cells contribute to the autoimmune process in atherosclerosis. Oral administration of oxLDL, which was identified as a candidate autoantigen in atherosclerosis, was shown to induce tolerance and suppress atherogenesis. However, the precise mechanisms of mucosal tolerance induction, in particular nasal tolerance, remain unknown. In this study, we explore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
46
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 40 publications
6
46
0
Order By: Relevance
“…In preclinical models, nasal or oral administration of HSP65 reduced atherosclerosis in Ldlr -/-mice (146,147). Similar findings are reported for nasal administration of oxLDL (148,149) or β2-glycoprotein I (150). Another approach is to deliver the relevant antigens via tolerogenic DCs that have suppressed costimulatory functions but maintain antigen-presenting functions.…”
Section: Regulation Of Proatherogenic Adaptive Immune Responsessupporting
confidence: 59%
“…In preclinical models, nasal or oral administration of HSP65 reduced atherosclerosis in Ldlr -/-mice (146,147). Similar findings are reported for nasal administration of oxLDL (148,149) or β2-glycoprotein I (150). Another approach is to deliver the relevant antigens via tolerogenic DCs that have suppressed costimulatory functions but maintain antigen-presenting functions.…”
Section: Regulation Of Proatherogenic Adaptive Immune Responsessupporting
confidence: 59%
“…Both IL-10 and TGF-β1 have been confirmed to exhibit antiatherogenic properties using different approaches including transfer gene models, knockout models, neutralization, and adenovirus expression vector 2, 3, 9 . In our previous studies, we also found that TGF-β plays a vital role in an oxLDL and thymic stromal lymphopoietin (TSLP) treated atherosclerosis prone model 25, 26, 35 . Because not blocking TGF-β1 signaling but blocking IL-10 signaling significantly abolished the protective effects of IL-37 in a myocardial I/R injury model 12 , and because the ascending range of IL-10 was more significant than TGF-β1 in the present study, the anti-IL-10R mAb was used to clarify whether IL-10 is indispensable for the protective role of IL-37 in atherosclerosis.…”
Section: Discussionmentioning
confidence: 88%
“…Once an antigen reaches the cervical lymph nodes, however, it is likely that immune responses to CNS antigens may be constrained by the same mechanisms associated with mucosal tolerance induction, including TGFβ production by T regulatory cells (Treg; ref. 28), production of antibodies that signal through inhibitory Fc receptors like CD32 (FcRIIB; ref. 29), and preferential presentation in germinal centers, resulting in skewing toward B-cell predominant responses (30).…”
Section: Redefining Cns Immune Privilegementioning
confidence: 99%